The 1940s house [videorecording (DVD)] - Pirie, Caroline Ross; Palmer, Geoffrey, 1927-2020- (PBS Home Video, 2004)
One modern family takes on the challenge of domestic life on Britain's home front in 1940s house, a re-creation of a World War II household. This time-travel experiment covers the period from the outbreak of war in 1939 to Victory Day in 1945, compressing the events of six wartime years into two months. Though the military threat is metaphorical, the privations are real and the pressures create tensions nonexistent in modern society.